(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The results of physical development and the determination of the harmonious development of 253 children of school age are presented. The main morphological and functional indicators of physical development were determined: height, body weight, chest circumference. A comprehensive assessment of physical development depending on gender and age was carried out. The results of the study of physical development, the determination of the harmony in the development of children, showed that at present, with the main patterns of growth and development remaining, we can talk about the process of retardation.